2018
DOI: 10.1152/ajpcell.00137.2018
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin induces dysfunction of fetal endothelial colony-forming cells from gestational diabetic pregnancies

Abstract: Fetal exposure to gestational diabetes mellitus (GDM) predisposes children to future health complications including hypertension and cardiovascular disease. A key mechanism by which these complications occur is through the functional impairment of vascular progenitor cells, including endothelial colony-forming cells (ECFCs). Previously, we showed that fetal ECFCs exposed to GDM have decreased vasculogenic potential and altered gene expression. In this study, we evaluate whether transgelin (TAGLN), which is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Transgelins are a family of proteins that were discovered decades ago ( Lees-Miller et al, 1987 ; Shapland et al, 1993 ). They are involved in many diseases, including asthma, hypertension, diabetes and cancer, but the role of transgelins in cancer is not very clear ( Huang et al, 2018 ; Sun et al, 2018 ; Varberg et al, 2018 ; Yin et al, 2018 ). Recently, studies have shown that transgelins are associated with CRC metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Transgelins are a family of proteins that were discovered decades ago ( Lees-Miller et al, 1987 ; Shapland et al, 1993 ). They are involved in many diseases, including asthma, hypertension, diabetes and cancer, but the role of transgelins in cancer is not very clear ( Huang et al, 2018 ; Sun et al, 2018 ; Varberg et al, 2018 ; Yin et al, 2018 ). Recently, studies have shown that transgelins are associated with CRC metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins (TAGLN and MGP) are expressed in smooth muscle cells of developing vasculature and most likely contribute to vasculogenic dysfunction of PE. 21 , 25 , 26 Similar to MGP and TAGLN, the differentially upregulated HSPG2 protein is also associated with vascularity. This extracellular matrix protein has an active role in vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary Human Endothelial Colony Formation Cells (ECFCs) were generously provided by Dr. Laura Haneline (IUSM). ECFCs were isolated from umbilical cord blood samples by the Indiana University Simon Cancer Center Angio BioCore and stored as previously described 66 . ECFC aliquots were thawed and cultured in endothelial growth media 2 (EGM2, Lonza America, Inc., Walkersille, MD) plus 10% FBS, plated on flasks coated with type 1 collagen (Corning, Inc., Durham, NC).…”
Section: Cell Culture Of Cell Lines and Primary Human Endothelial Colmentioning
confidence: 99%